Regular treatment with formoterol and an inhaled corticosteroid versus regular treatment with salmeterol and an inhaled corticosteroid for chronic asthma: serious adverse events - O'Shea, Orlagh (Cochrane Database Syst Rev, 2021)
BACKGROUND: Asthma is characterised by chronic inflammation of the airways and recurrent exacerbations with wheezing, chest tightness, and cough. Treatment with inhaled steroids and bronchodilators can result in good control of symptoms, prevention of further morbidity, and improved quality of life. However, an increase in serious adverse events with the use of both regular formoterol and regular salmeterol (long‐acting beta₂‐agonists) compared with placebo for chronic asthma has been demonstrated in previous Cochrane Reviews. This increase was statistically significant in trials that did not randomise participants to an inhaled corticosteroid, but not when formoterol or salmeterol was combined with an inhaled corticosteroid. The confidence intervals were found to be too wide to ensure that the addition of an inhaled corticosteroid renders regular long‐acting beta₂‐agonists completely safe; few participants and insufficient serious adverse events in these trials precluded a definitive decision about the safety of combination treatments. OBJECTIVES: To assess risks of mortality and non‐fatal serious adverse events in trials that have randomised patients with chronic asthma to regular formoterol and an inhaled corticosteroid versus regular salmeterol and an inhaled corticosteroid. SEARCH METHODS: We searched the Cochrane Airways Register of Trials, CENTRAL, MEDLINE, Embase, and two trial registries to identify reports of randomised trials for inclusion. We checked manufacturers' websites and clinical trial registers for unpublished trial data, as well as Food and Drug Administration (FDA) submissions in relation to formoterol and salmeterol. The date of the most recent search was  24 February 2021. SELECTION CRITERIA: We included controlled clinical trials with a parallel design, recruiting patients of any age and severity of asthma, if they randomised patients to treatment with regular formoterol versus regular salmeterol (each with a randomised inhaled corticosteroid) and were of at least 12 weeks' duration. DATA COLLECTION AND ANALYSIS: Two review authors independently selected trials for inclusion in the review, extracted outcome data from published papers and trial registries, and applied GRADE rating for the results. We sought unpublished data on mortality and serious adverse events from study sponsors and authors. The primary outcomes were all cause mortality and non‐fatal serious adverse events. We chose not to calculate an average result from all the formulations of formoterol and inhaled steroid, as the doses and delivery devices are too diverse to assume a single class effect. MAIN RESULTS: Twenty‐one studies in 11,572 adults and adolescents and two studies in 723 children met the eligibility criteria of the review. No data were available for two studies; therefore these were not included in the analysis. Among adult and adolescent studies, seven compared formoterol and budesonide to salmeterol and fluticasone (N = 7764), six compared formoterol and beclomethasone to salmeterol and fluticasone (N = 1923), two compared formoterol and mometasone to salmeterol and fluticasone (N = 1126), two compared formoterol and fluticasone to salmeterol and fluticasone (N = 790), and one compared formoterol and budesonide to salmeterol and budesonide (N = 229). In total, five deaths were reported among adults, none of which was thought to be related to asthma. The certainty of evidence for all‐cause mortality was low, as there were not enough deaths to permit any precise conclusions regarding the risk of mortality on combination formoterol versus combination salmeterol. In all, 201 adults reported non‐fatal serious adverse events. In studies comparing formoterol and budesonide to salmeterol and fluticasone, there were 77 in the formoterol arm and 68 in the salmeterol arm (Peto odds ratio (OR) 1.14, 95% confidence interval (CI) 0.82 to 1.59; 5935 participants, 7 studies; moderate‐certainty evidence). In the formoterol and beclomethasone studies, there were 12 adults in the formoterol arm and 13 in the salmeterol arm with events (Peto OR 0.94, 95% CI 0.43 to 2.08; 1941 participants, 6 studies; moderate‐certainty evidence). In the formoterol and mometasone studies, there were 18 in the formoterol arm and 11 in the salmeterol arm (Peto OR 1.02, 95% CI 0.47 to 2.20; 1126 participants, 2 studies; moderate‐certainty evidence). One adult in the formoterol and fluticasone studies in the salmeterol arm experienced an event (Peto OR 0.05, 95% CI 0.00 to 3.10; 293 participants, 2 studies; low‐certainty evidence). Another adult in the formoterol and budesonide compared to salmeterol and budesonide study in the formoterol arm had an event (Peto OR 7.45, 95% CI 0.15 to 375.68; 229 participants, 1 study; low‐certainty evidence). Only 46 adults were reported to have experienced asthma‐related serious adverse events. The certainty of the evidence was low to very low due to the small number of events and the absence of independent assessment of causation. The two studies in children compared formoterol and fluticasone to salmeterol and fluticasone. No deaths and no asthma‐related serious adverse events were reported in these studies. Four all‐cause serious adverse events were reported: three in the formoterol arm, and one in the salmeterol arm (Peto OR 2.72, 95% CI 0.38 to 19.46; 548 participants, 2 studies; low‐certainty evidence). AUTHORS' CONCLUSIONS: Overall, for both adults and children, evidence is insufficient to show whether regular formoterol in combination with budesonide, beclomethasone, fluticasone, or mometasone has a different safety profile from salmeterol in combination with fluticasone or budesonide. Five deaths of any cause were reported across all studies and no deaths from asthma; this information is insufficient to permit any firm conclusions about the relative risks of mortality on combination formoterol in comparison to combination salmeterol inhalers. Evidence on all‐cause non‐fatal serious adverse events indicates that there is probably little to no difference between formoterol/budesonide and salmeterol/fluticasone inhalers. However events for the other formoterol combination inhalers were too few to allow conclusions. Only 46 non‐fatal serious adverse events were thought to be asthma related; this small number in addition to the absence of independent outcome assessment means that we have very low confidence for this outcome. We found no evidence of safety issues that would affect the choice between salmeterol and formoterol combination inhalers used for regular maintenance therapy by adults and children with asthma.